Composition and generation of Municipal Solid Waste (MSW) in Malaysia: Balakong City case study - Abu Samah, Mohd Armi; Victor, Dennis; Dawda, Badgie; Abd Manaf, Latifah; Syed Ismail, Sharifah Norkhadijah; Abd Hamid, Khairul Bariyah; Yunus, Kamaruzzaman; Kamarudin, Mohd Khairul Amri (Herald NAMSCA, 2019)
Municipal Solid Waste (MSW) management is one of the most challenging issues faced by most developing countries. Knowledge of solid waste generation and composition is necessary for accurate decision-making in terms of engineering design, planning and forecasting for the management strategy of urban waste. The objective of this study was to determine MSW generation and composition in an urban area of Balakong City, Selangor, Malaysia. The application of a linear model on solid waste forecasting was also performed in this study. A survey of household residents in eight housing areas in Balakong was carried out for one month from January to February 2011. Data were collected on a daily basis. In total, organic waste was the highest composition (5,344 kg, 68.6%) among the solid waste generated in all eight housing areas. Plastic and paper comprised of 10.4% (811 kg) and 9.5% (736 kg) of the solid waste generated. The least composition was glass (270 kg, 3.5%) and metals (204 kg, 2.5%). Other type of disposables comprised of 5.5% (419 kg) of the total solid waste generated. A linear model on solid waste forecasting has determined slightly higher prediction on solid waste generation with a statistically significant difference was obtained at p < 0.05.